Refining the diagnosis of Huntington Disease: The PREDICT-HD study - Biglan, Kevin M.; Zhang, Ying; Long, Jeffery; Geschwind, Michael; Kang, Gail; Killoran, Annie; Lu, Wenjing; McCusker, Elizabeth; Mills, James A.; Raymond, Lynn A.; Testa, Claudia; Wojcieszek, Joanne; et al. (Frontiers in Aging Neuroscience, 2013)
Participants with the gene expansion for Huntington disease (HD) but not yet diagnosed were evaluated annually. Unidimensional diagnosis (UD) was a motor diagnosis defined as a diagnostic confidence level (DCL) of 4 (unequivocal motor signs, ≥99% confidence) on the standardized motor exam of the Unified Huntington Disease Rating Scale (UHDRS). Multidimensional diagnosis (MD) was defined as answering yes on Question 80 (Q80) of the UHDRS, ≥99% confidence of manifest HD based on the entire UHDRS. Motor, cognitive, and behavioral measures of phenotype at first diagnosis were compared by t-tests between participants diagnosed via motor exam (UD) and those diagnosed via multidimensional input (MD). Cluster analysis identified clusters based on UHDRS domains.186 participants received a diagnosis of HD during a maximum of 6.4 years of follow- up. In 108 (58.1%) the diagnosis by MD and UD occurred simultaneously, while in 69 (37.1%) the diagnosis by MD occurred prior to UD. Participants who were diagnosed by MD prior to UD were less impaired on motor (12.2±6.7 vs 22.4±9.3, p<0.0001), and cognitive (290.7±56.2vs 258.0±53.7, p=0.0002), but not behavioral measures (16.3±21.2 vs 18.6±22.1, p=0.49) when compared with those diagnosed simultaneously. Cluster analysis identified three clusters that represented primarily cognitively impaired, behaviorally impaired, and cognitively preserved phenotypes. A multidimensional method results in an earlier diagnosis with less motor and cognitive impairment than a motor diagnosis. Findings have implications for designing preventive trials and providing clinical care in prodromal HD.